2008 Global Financial Recession Impact on Yemen’s Economy and Oil Industry - Gaghman, Abdulghani (Technium Social Sciences Journal, 2021)
Yemen as an oil exporting country with relatively larger populations and modest oil resources has witnessed a sharp deterioration in their public finances and current account balances in 2008-2009, as a result of financial crisis mainly lower oil prices leading to a weakening of the economy.This study targeting the global crisis impact on Yemen’s economy, by analysis the macroeconomic indicators to understand how much the government achieve in term of economic efficiency which reflected in economic growth, full employment, trade balance and price stability. Yemen has less developed monetary banking system and relatively minor exposure to foreign banks, which result in fair impact from the financial global crisis. However, the government can’t sustain exchange rate and stabilize the price the non-oil declined by 3% of the determined gross domestic product (GDP) in 2009, from 6.98% in 2008. This paper found that the crisis has negative impact on the government revenues, trade balance and significant reduction in foreign direct investment (FDI), caused reduction in spending and widened the deficits in the budget and the balance of payments. Real growth has been achieved relatively high rates and through precisely the crisis. The revenues declined more than 10% in 2009 and government expenditures reduced with regards to decline in oil revenues and service delivery. The government responses were successful in the monetary policy side, but with lots of blurred in the fiscal policies which was subject for critical discussion and assessment. This paper concluded that to improve the overall Yemen’s economy and avoid any unpleasant economic event in the future, government should have a strategic plan to achieve sustain growth rate by diverse outcome resources, support the private sector and encourage investments.